Current status and trajectories of e-government in Iceland based on international measurement systems - Haukur Arnþórsson; Ómar H. Kristmundsson (Veftímaritið Stjórnmál og stjórnsýsla, 2012)
The article discusses the present status and developments of e-government in Iceland as described by international measurement systems. A Nordic comparison is performed. The methodology used in collection of international data are defined. Potential explanations for the current status and trajectories of e-government in Iceland are discussed. The findings indicate that all the necessary conditions for advanced e-government exist in Iceland, e.g. general internet use, a high education level and necessary telecommunication structure. However, the results suggest that e-governmental services are significantly deficient as is the coordination of information and services. The government has therefore not been able to use these preconditions to improve public service and citizen e-participation by using e.g. social media. Because of increasing public demand for accessible government information and participation in government decision making, the present status can influence public mistrust towards government.